2023
DOI: 10.1186/s12936-023-04596-1
|View full text |Cite
|
Sign up to set email alerts
|

Poor performance of malaria rapid diagnostic tests for the detection of Plasmodium malariae among returned international travellers in China

Abstract: Background Malaria is a worldwide infectious disease. For countries that have achieved malaria elimination, the prevention of re-establishment due to infections in returned travellers has become important. The accurate and timely diagnosis of malaria is the key in preventing re-establishment, and malaria rapid diagnostic tests (RDTs) are frequently used due to their convenience. However, the RDT performance in Plasmodium malariae (P. malariae) infection diagnosis remains unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…[14]. Notably, RDTs have lower sensitivity for P. vivax compared with Plasmodium falciparum (P. falciparum) [15]. In the midst of these challenges, we observed that the iRBC flags in the hematology results were not affected, mainly due to significant changes in erythrocytes during parasitic infections.…”
Section: Discussionmentioning
confidence: 81%
“…[14]. Notably, RDTs have lower sensitivity for P. vivax compared with Plasmodium falciparum (P. falciparum) [15]. In the midst of these challenges, we observed that the iRBC flags in the hematology results were not affected, mainly due to significant changes in erythrocytes during parasitic infections.…”
Section: Discussionmentioning
confidence: 81%
“…In cases of P. malariae malaria, misdiagnosis is linked to the poor performance of RDTs, underlined in the majority of manufactured RDT [15].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wu et al reported that RDT had a low detection rate (56.5%) among P. malariae cases from returned international travelers in China [ 5 ]. Overall, the sensitivity of RDTs greatly depends on the parasitemia of the samples [ 5 , 6 , 7 ]. To date, there is no RDT for the specific detection of P. knowlesi samples available on the market.…”
Section: Introductionmentioning
confidence: 99%